ANALISIS LINGKUNGAN PEMASARAN GLOBAL TERHADAP STRATEGI PEMASARAN PERUSAHAAN MULTINASIONAL DI ERA DIGITALISASI - Saragih, Lenti Susanna; Nabanan, Eskawati; Anggun, Nurma; Pangaribun, Indah Yesica; Simorangkir, Naomi Stephania (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the influence of the global marketing environment on the marketing strategies of multinational companies in the digitalization era. Technological changes, global competition, and consumer behavior encourage companies to adapt their marketing strategies through the use of digital media and product innovation. The research method used is descriptive qualitative with a literature study approach from various scientific sources. The results show that digitalization helps companies expand markets, improve communication with consumers, and strengthen global competitiveness.